KEPENTINGAN INDONESIA BEKERJASAMA DENGAN MALAYSIA DI BIDANG KELAUTAN DAN PERIKANAN TAHUN 2013-2016 (STUDI KASUS: PERAIRAN NATUNA) - Novella Putri Lerian; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study examines the Importance of Indonesia Cooperate With Malaysia in Marine and Fishery Field 2013-2016. The rise of illegal fishing practices (IUU Fishing) has made the Government of Indonesia take policy in eradicating IUU Fishing that occurred at the border of Indonesian waters, one of them in Natuna Waters which is very vulnerable due to the direct border with The South China Sea and Malaysia Waters and other Neighbor Countries.The method used in this research is qualitative research. The data obtained comes from books, journals, theses, articles, internet sites and other sources related to research. The focus of this research is why Indonesia is working with Malaysia in the field of marine and fisheries in Natuna waters. This research uses the perspective of neo-realism. The theory used is the theory of international cooperation and the theory of national interest.Natuna waters are an exclusive zone of ZEE (exclusive economic zone) of marine resources. Indonesia and Malaysia signed a Memorandum of Understanding (MOU) on 27 January 2012 in Nusa Dua, Bali to deal with fishermen who tried to practice illegal fishing. (MoU) of the Common Guidelines Concerning Treatment of Fishermen by Maritime Law Enforcement Agencies. Then Indonesia can maintain the sovereignty of the State and marine resources, and improve the Indonesian economy in the export sector of fish products.Keywords: IUU Fishing, Theory International Cooperation, Exclusive Economic Zone